Optimization of hydro distillation conditions for the production of essential oil from Alpinia galanga - Shahril, Mohamad (2006)
Essential oils from the rhizomes of Alpinia galanga are primarily used in the perfumery industry and have a very high commercial value due to its therapeutic properties. As essential oils are composed of heat-sensitive chemical compounds, the use of conventional steam distillation technique would inevitably inflict thermal degradation to the natural fragrance. In this experimental work, hydro distillation method was employed due to its milder extracting condition and lower operating cost. Three different mesh sizes were used, named herein as powder, cubes (1cmx1cmx1cm) and slices, respectively. The extract compositions were compared using gas chromatography analysis. Besides mesh size, further studies also revealed that the composition and yield of essential oils were influenced by the different types of solvents used. The most optimum yield which is 0.79% was extracted from powder sample with n-hexane as solvent. The low yield of essential oils can be improved in future studies by carrying out the research on a larger scale.